ERGONOMIC WORKPLACE FOR QUALITY AND PRODUCTION IMPROVEMENT - Gempur Santoso (Bajang Institute, 2022)
Ergonomic workplace is needed to improve quality and production. This paper wants to discuss how to create an ergonomic production workplace so as to improve product quality. This paper is designed using a literature study, which uses several references or literature related to ergonomics, production processes, and the quality or quality of work and products. This paper is written descriptively or data presentation or literature from several opinions and findings. Then analyzed descriptively qualitatively. Conclusion: First, that the production site can create ergonomics, as follows: a) the production site must be ergonomically designed so that employees do not get tired easily, do not leave work, do not get hurt, and can increase work productivity; b) the production site can be created ergonomically so that all equipment is adjusted to the anthropometric dimensions of the user or employee. Or, all equipment used by employees needs to be made that can be adjusted (adjustable) to adapt the equipment to human users (employees); c) the environment needs to be made ergonomically, namely the physical environment according to the provisions of the threshold value (NAV), and the chemical and biological environment according to quality standards; d). employees will feel ergonomic if they are protected from psychological/psychic pressure and heat stress; and e). the application of ergonomics in the company will be implemented if there is a commitment from all parties in the company and especially management commitment. Second: a). quality improvement will occur if customer satisfaction occurs, and employees need to have good character and are experts in the field of product production; b). the application of ergonomics in the manufacturing (production) process will improve product quality, reduce production costs, and are needed by customers.